Intra-communal conflicts & the politics of oil compensation sharing among indigenes of llaje community, Ondo State, Nigeria (2015)
Payment and distribution of oil compensation as a benefit for oil exploration impact has often resulted in communal conflicts between and within oil producing communities of Ilaje coastal area of Ondo State, Nigeria. This study examined local politics and conflict inherent in oil compensation agitation and distribution in relevant communities. It synthesized Joseph prebendalism theory and Mills' elite theory as its theoretical base with specific emphasis on the local politics on agitation, negotiation and distribution of oil compensation. Thirteen communities were purposively selected from the coastal communities. Qualitative data collection methods were mainly employed for this research. These included In-depth interviews with traditional leaders, Focus Group Discussions among community youth leaders and Key Informant Interviews were done amongst community representatives. Data collection was complemented with a community survey to capture the views of community members. Increase in conflict and agitation for oil compensation in oil producing communities arose from differentials in oil compensation categories in the study area which deepened oil politics and conflicts arising from the prebendal roles of the elites and traditional rulers. The work suggested more proactive measures for restructuring oil compensation payment and distribution.